2018
DOI: 10.3390/f9050276
|View full text |Cite
|
Sign up to set email alerts
|

Solid Wood Properties Assessed by Non-Destructive Measurements of Standing European Larch (Larix decidua Mill.): Environmental Effects on Variation within and among Trees and Forest Stands

Abstract: Abstract:To avoid unintentional loss of wood quality when selecting for higher productivity in tree breeding programs, non-destructive methods for fast and reliable assessment of wood quality on standing trees are required. In this study, we tested and applied Pilodyn penetration (PP) and measures of stress wave velocity (SWV) in trees within a European larch (Larix decidua Mill.) breeding program. Through testing PP in 4267 trees on 21 afforestation sites across a broad climatic spectrum, we analysed the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A number of factors have been reported to affect VEL measurements on standing trees such as the presence of knots, compression wood [45], spiral grain [46], age [47], temperature [48], moisture content [49][50][51], or direction of the measurement on sloping terrain [52]. It has also been observed that VEL can be influenced by insertion depth of probes [53], their imbedding angle [54], and variation in hitting intensity [45].…”
Section: Factors Affecting Acoustic Velocity Measurementsmentioning
confidence: 99%
“…A number of factors have been reported to affect VEL measurements on standing trees such as the presence of knots, compression wood [45], spiral grain [46], age [47], temperature [48], moisture content [49][50][51], or direction of the measurement on sloping terrain [52]. It has also been observed that VEL can be influenced by insertion depth of probes [53], their imbedding angle [54], and variation in hitting intensity [45].…”
Section: Factors Affecting Acoustic Velocity Measurementsmentioning
confidence: 99%
“…For example, at belowground level, (mini) rhizotrons and ground-penetrating radar allows for evaluating tree rooting distribution and growth [17,18]. Moreover, at aboveground level, NDT measures allow for evaluation of the mechanical and technological properties of standing trees [19][20][21][22]. More specifically, stress wave-based non-destructive acoustic techniques have been extensively investigated during the past few decades [23], resulting in very useful methods for predicting the mechanical properties of woody materials.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, two linear regression models to estimate softwood and hardwood specimen density separately using drilling residue mass as a predictor variable were developed.In both models, the assumptions of normality, homoscedasticity and linearity were tested. The resulting models are shown in Equations (4) and (5). Where "ρ" is the specimen density in kg m −3 and "dr mean " is the drilling residue mean mass in g (including the filter bag).…”
Section: Resultsmentioning
confidence: 99%
“…To retrofit the existing timber structures with renovation and restoration works, it is previously necessary the characterization of wood singularities (knots, cracks, etc. ), biologic degradation, and the estimation of the mechanical properties [1][2][3][4][5][6]. Non-destructive and semi-destructive testing (NDT/SDT) includes accurate, dependable and easy to use techniques for estimation of timber mechanical properties in the assessment of existing timber structures [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%